Interrupted Fertility - Taylor, Dr (Res Medica, 2014)
Mrs Buff, wife of Mr Buff, silk weaver in Fashion Street in Spitafields, London, aged twenty-seven years the mother of several childerine, on 27th of July 1774, having gone her usual time of pregnancy, was attended by her midwife several days, but the labour pains ceasing, the midwife left her promising to return soon but did not fulfil her promise. Mrs B. not being delivered of her child, thought she might have a month longer to go and went about her domestic affairs as usual. Christmas following she prov’d with child again and not being delivered of the former one she became uncommonly big and unwieldly, she applied to several physicians for advice and particularly to Dr. Wyman an eminent man midwife in Aldermanbury, who ordered her a variety of purgative medicines but without relief.